Musical traditions and cultural identities in dispute: rethinking the Azorean identity discourse of Santa Catarina through the musicality of Boi de Mamão (Orfeu, 2025)
This paper aims to reflect on the discourse of Azorean identity, which began on the Santa Catarina, Brazil, in the 1950s. We intend to build this investigation based on the musicality of Boi de Mamão, a cultural tradition originating from the region and one of the contemporary symbols of its identity. This will be done through analyses of historical records, rhythmic elements and comparisons with musical manifestations from other Brazilian regions, as well as from the Azorean islands, Portugal. Based on ethnomusicology, the paper is divided into three parts: the first part discusses the narratives of origin and musicality of the Boi de Mamão, comparing it with other similar traditions in Brazil and abroad; the second part brings discussions about the discourse of Azorean identity on the Santa Catarina coast, problematizing the unilateral and hiding narrative of identity construction that often supports this discourse; and, finally, the third part discusses approximations between the cultural identity of the Santa Catarina coast with the cultural universes of the Caiçara people, in the States of Paraná, São Paulo and Rio de Janeiro. Therefore, the present work proposes to point out these possible historical traces of indigenous and Afro-Brazilian traditions that marked the musicality of Boi de Mamão and the cultural identity of Santa Catarina.